The Development and Educational Inheritance of Li Pottery as a Carrier of Local Wisdom in the Context of Modernity - Zhang, Tieli; Sirisuk , Mateta (Journal of Practical Studies in Education, 2025)
Li Pottery, a distinctive traditional craft of the Hainan Li ethnic group, serves as a vital carrier of local wisdom, encompassing ecological adaptation, cultural values, and community identity. In the context of increasing modernization, traditional knowledge systems embedded in Li Pottery face both challenges and opportunities for transformation. This study explores the development and educational inheritance of Li Pottery, emphasizing its function as a medium for transmitting indigenous knowledge across generations. Adopting a qualitative research approach, the study integrates literature review and ethnographic fieldwork, including site observations and interviews with artisans and community members. The findings reveal that Li Pottery-making is intricately linked to local natural resources, matrilineal knowledge transmission, and socio-cultural structures, characterized by techniques such as tray-building and open-air firing. While modernization threatens the continuity of traditional practices, it also offers possibilities for educational innovation and cultural revitalization. The study underscores the importance of embedding Li Pottery into contemporary educational frameworks to ensure sustainable cultural transmission. By positioning Li Pottery as both a cultural product and an educational tool, this research contributes to the discourse on safeguarding intangible cultural heritage and fostering intercultural learning in modern contexts.